Perlindungan Hukum bagi Warga Negara Asing dalam Pembagian Hak Waris Terkait Hak Milik Tanah di Indonesia - Sibarani, Christine Martha Rinauly; Franciska, Wira; Marniati, Felicitas Sri (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Differences in nationalities between inheritors and heirs do not invalidate a person's right to inherit. Phenomenon in society, heirs of foreigners did not inherit ownership rights to land. This research aims to analyze the position of heirs of foreigners who receive the inheritance of land ownership rights and to analyze the legal protection of inheritance rights for land ownership rights received by foreigners. The theory used in this research is the Legal Protection Theory by Soetjipto Raharjo and the Inheritance Theory by Wirjono Prodjodikoro. The research method used is normative juridical. The conclusion is foreign heirs still have the right to inherit, for inherited in the land of Ownership Rights, some provisions must be complied with by UUPA that foreigners are obliged to relinquish ownership rights to land within one year from the acquisition of these rights, within that period foreigners can be transferred or sell the land ownership rights to another heir or other parties, or decrease the right to be right to use. After this period, the rights are extinguished because the law and the land belong to the State. However, foreign heirs can be given the right to occupy (including the rights to use, manage, and relish economically), because there is no prohibition in positive legal provisions for a foreigner to occupy and receive economic benefits from a house or building object.